Evaluation of Cerebral Aneurysms with High-Resolution MR Angiography Using a Section-Interpolation Technique: Correlation with Digital Subtraction Angiography - Chung, Tae-Sub; Joo, Jin-Yang; Lee, Seung-Koo; Chien, Daisy; Laub, Gerhard (American Journal of Neuroradiology, 1999)
BACKGROUND AND PURPOSE: The objective was to evaluate the results of high-resolution, fast-speed, section-interpolation MR angiography and digital subtraction angiography (DSA), thereby examining the potential use of a primary noninvasive screening test for intracranial aneurysms.METHODS: The images were obtained in 39 cerebral aneurysmal lesions from 30 patients with a time-of-flight MR angiographic technique using a 1.5-T superconducting MR system. The total image volume was divided into four slabs, with 48 partitions each. To save time, only 24 phase-encoded steps were measured and interpolated to 48. The parameters used included 30/6.4 (TR/TE), a flip angle of 25°, a 160 × 512 matrix, a field of view of 150 × 200, 7 minutes 42 seconds of scan time, an effective thickness of 0.7 mm, and an entire thickness of 102.2 mm. Maximum intensity projection was used for the image analysis, and a multiplanar reconstruction technique was used for patients with intracranial aneurysms.RESULTS: Among 39 intracranial aneurysmal lesions in 30 patients, 21 were ruptured and 18 were unruptured. Twelve lesions were less than 2 mm in size, 12 were 3 to 5 mm, 12 were 6 to 9 mm, and three were larger than 10 mm. At initial examinations, 38 of 39 aneurysmal lesions were detected by both MR angiography and DSA, with 97% sensitivity. In confirming aneurysms in neck and parent vessels, multiplanar reconstruction was successful in detecting all 39 aneurysms, whereas MR angiography was successful in detecting 27 (69%) and DSA was successful in detecting 32 (82%) of the lesions.CONCLUSION: High-resolution MR angiography with a section-interpolation technique showed equal results to those of DSA for the detection of intracranial aneurysms and may be used as a primary noninvasive screening test. In the evaluation of aneurysms in neck and parent vessels, the concurrent use of MR angiography and multiplanar reconstruction was far superior to the use of either MR angiography or DSA alone.